2008
DOI: 10.1037/0097-7403.34.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery of extinguished fear responses deepens their extinction: A role for error-correction mechanisms.

Abstract: A series of experiments used a within-subject design to study spontaneous recovery of fear responses (freezing) to an extinguished conditioned stimulus (CS) in rats. Experiments 1, 2, 3, and 4 demonstrated that: a remotely extinguished CS elicited more freezing than a recently extinguished one on a common test; that the CS showing recovery underwent greater response loss across additional extinction than the one lacking recovery; and that spontaneous recovery and deepening of response loss survived recondition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 34 publications
6
57
0
Order By: Relevance
“…One such manipulation is the passage of time between nonreinforced exposures, which has been suggested to promote further inhibitory learning by restoring prediction error when an already exposed stimulus is given additional exposures (Leung and Westbrook, 2008). Consistent with this suggestion, in latent inhibition, rats given an initial bout of preexposure to a stimulus and then given additional exposures after a passage of time showed more latent inhibition than a stimulus given equivalent but successive exposures (Holtzman et al, 2010).…”
Section: Introductionsupporting
confidence: 58%
“…One such manipulation is the passage of time between nonreinforced exposures, which has been suggested to promote further inhibitory learning by restoring prediction error when an already exposed stimulus is given additional exposures (Leung and Westbrook, 2008). Consistent with this suggestion, in latent inhibition, rats given an initial bout of preexposure to a stimulus and then given additional exposures after a passage of time showed more latent inhibition than a stimulus given equivalent but successive exposures (Holtzman et al, 2010).…”
Section: Introductionsupporting
confidence: 58%
“…Rescorla (2003) also found that response loss to a cue extinguished in compound with a familiar but neutral stimulus was greater than that to a cue extinguished in compound with a conditioned inhibitor. Finally, Leung and Westbrook (2008) reported greater loss of responding to a cue that was extinguished in compound with an extinguished cue undergoing spontaneous recovery (error was large) than to a second cue extinguished in compound with an extinguished cue not undergoing recovery (error was small).…”
Section: Introductionmentioning
confidence: 99%
“…Just as extinction leaves intact the excitatory association produced by conditioning, recent evidence also shows that reconditioning an extinguished CS leaves intact the inhibitory association produced by extinction. For instance, such a CS continues to exhibit the signature phenomena of extinction such as spontaneous recovery (Rescorla 2001;Leung and Westbrook 2008). This implies that the learning that produces these phenomena survives reconditioning in spite of the fact that the CS now elicits fear responses (see Rescorla [2001], for discussion).…”
mentioning
confidence: 99%